Investigation in the field of intensification of mass transfer processes in vacuum pans - Garyazha, Vladimir; Artyuhov, Yuri; Kulinchenko, Vitaliy; Didushko, Boris (My University, 1978)
On the basis of investigations in the field of hydrodynamics and heat exchange during boiling of massecuite in tubes a new hydrodynamic methods of intensified mass exchange while crystallisation by the way of blowing gas, steam or their mixture into boiling tubes of vacuum pans have been developed.

На підставі досліджень у сфері гідродинаміки і теплообміну при кипінні утфелів у кип’ятильних трубах запропоновані гідродинамічні методи підсилення масообміну, під час кристалізації шляхом вдування газу, пари або їх суміші в киплячі утвеля у вакуум-апарати.
Keywords: hydrodynamics; heat exchange vakuum-pan; crystallization; гідродинаміка; теплообмін вакуум-апарат; кристалізація; кафедра процесів і апаратів харчових виробництв